“Pengaruh Advertising Value pada Youtube Advertising terhadap Purchase intentions pada produk Telkomsel dengan Brand Awareness sebagai Variabel Mediasi “(Studi pada Mahasiswa Universitas Brawijaya yang Menonton Iklan Telkomsel #TraktirNasional di Youtube) - Maulana, Ahmad Fahmi (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims to know the influence of the advertising value and brand awareness against the purchase intention products telkomsel at Brawijaya University students good influence directly or indirectly. This research type is explanatory research that explains the causal relationships between variables through hypothesis testing.This research using a sample of as many as 120 respondents drawn from a population of  University  students  of  Brawijaya.  Sampling purposive  sampling  technique  using characteristics of the selected sample i.e., at least 17 years old, and have never made a purchase of product Telkomsel. Testing tool used to test the research instrument in the form of test validity, reliability testing, and test assumptions. Hypothesis testing is done using t- test and test the Sobel test. Data analysis techniques using the analysis of PLS (Partial Least Squares) and test the hypothesis done using t-test using the program Smasrt PLS 3.0. From the results it can be concluded that variable advertising value had a direct influence significantly to brand awareness product of telkomsel. Brand Awareness also has direct influence significantly to Purchase Telkomsel product Intention. As well as variable advertising value has a positive and significant influence towards purchase intention on the product brand awareness with telkomsel as mediation variablesKEYWORDS: Advertising Value, Brand Awareness, Purchase Intention